2006
DOI: 10.1088/0964-1726/15/4/002
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniformly polarized piezoelectric modal transducer: fabrication method and experimental results

Abstract: The study of modal sensors and actuators is motivated by their ability to control the resonance frequency and the vibration modes of mechanical structures. In this work, a non-homogeneous poling method to obtain a radial modal sensor from a piezoelectric disc is presented. The construction method for three modal elements is described and their electrical behavior is presented and analyzed in comparison to a uniform poled disc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
1
10
0
1
Order By: Relevance
“…8 It was confirmed that the presented model succeeds in explaining the modal behavior of the Bessel transducer, a fact arisen from the comparison of theoretical and experimental results obtained for the three particular Bessel transducers. This is based on extending the MOT model 1 by assuming radial dependence in the piezoelectric coefficients.…”
supporting
confidence: 69%
“…8 It was confirmed that the presented model succeeds in explaining the modal behavior of the Bessel transducer, a fact arisen from the comparison of theoretical and experimental results obtained for the three particular Bessel transducers. This is based on extending the MOT model 1 by assuming radial dependence in the piezoelectric coefficients.…”
supporting
confidence: 69%
“…Instead of using multiple discrete concentric PZT elements, it is shown that constructing a UTET using a commercially available disc shape PZT element in which both opposing faces are initially fully coated by electrodes and then partitioning one surface electrode into six concentric electrodes is feasible. This is a most practical approach for the transmitter fabrication, rather than using complex shading of the piezoelectric polarization as suggested in [16,17]. Nevertheless, this newly proposed approach implies usage of a power amplifier array.…”
Section: Discussionmentioning
confidence: 99%
“…Radial surface velocity distribution may be attained through several approaches, such as uniform excitation of a transducer with a radial distribution of the level of piezoelectric polarization [16,17], or use of a non-uniform radial excitation of a transducer composed of an array of concentric rings surrounding an inner concentric disc [18]. The second approach was chosen since it does not involve a complex piezoelectric material polarization procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Optimum amplitude and half-width time values of the rectangular pulses are found by the L2 criterion [15,16]: L n 2 ðU X 0 BLn ; U RBLn Þ ¼ min 20log 10 ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi P M j¼1 ½U X 0 BLn ðx j Þ À U RBLn ðp n ; s n ; x j Þ 2…”
Section: Theoretical Backgroundunclassified
“…In our approach, theoretical X-wave electrical excitations are approximated with rectangular pulses, by means of applying the criterion of the L2 curve [15,16]. This allows carry out an optimization of the approaching of the X-wave driving signals pattern (by certain simpler rectangular pulses), in order to minimize the differences between their effects on emitted signals, by means of the adjustment of the main pulse parameters.…”
Section: Introduction and Some Antecedentsmentioning
confidence: 99%